Development of Energy Consumption Measurement and Monitoring System for Household Applications - Muhammad Armie Ariffudin Zaidi; Azlina Bahari; Zurina Abdul Wahab (Progress in Engineering Application and Technology, 2024)
The existing electricity bill only calculated the monthly usage for the entire house. Because of this, consumers do not know where the electrical energy is being used. "Measuring Energy Consumption" project aims to address these issues by designing a system to monitor the trend of energy consumption of electrical appliances in households with their estimated cost (RM) per month through smartphones. ESP32 is used as the microcontroller of the project, and the PZEM-004T V3 module is utilised to obtain the readings of energy, power, voltage, current, frequency, and power factor of the electrical appliances. The reading can be displayed through Blynk on both desktops and smartphones. The graphical visualisation of the data that has been gathered can also be done with Blynk to ease the process of analysing the trend of energy consumption of electrical appliances in households.